Nanoplatforms Targeting Intrinsically Disordered Protein Aggregation for Translational Neuroscience Applications - Chih Hung Lo; Lenny Yi Tong Cheong; Jialiu Zeng (Nanomaterials)
Intrinsically disordered proteins (IDPs), such as tau, beta-amyloid (Aβ), and alpha-synuclein (αSyn), are prone to misfolding, resulting in pathological aggregation and propagation that drive neurodegenerative diseases, including Alzheimer’s disease (AD), frontotemporal dementia (FTD), and Parkinson’s disease (PD). Misfolded IDPs are prone to aggregate into oligomers and fibrils, exacerbating disease progression by disrupting cellular functions in the central nervous system, triggering neuroinflammation and neurodegeneration. Furthermore, aggregated IDPs exhibit prion-like behavior, acting as seeds that are released into the extracellular space, taken up by neighboring cells, and have a propagating pathology across different regions of the brain. Conventional inhibitors, such as small molecules, peptides, and antibodies, face challenges in stability and blood–brain barrier penetration, limiting their efficacy. In recent years, nanotechnology-based strategies, such as multifunctional nanoplatforms or nanoparticles, have emerged as promising tools to address these challenges. These nanoplatforms leverage tailored designs to prevent or remodel the aggregation of IDPs and reduce associated neurotoxicity. This review discusses recent advances in nanoplatforms designed to target tau, Aβ, and αSyn aggregation, with a focus on their roles in reducing neuroinflammation and neurodegeneration. We examine critical aspects of nanoplatform design, including the choice of material backbone and targeting moieties, which influence interactions with IDPs. We also highlight key mechanisms including the interaction between nanoplatforms and IDPs to inhibit their aggregation, redirect aggregation cascade towards nontoxic, off-pathway species, and disrupt fibrillar structures into soluble forms. We further outline future directions for enhancing IDP clearance, achieving spatiotemporal control, and improving cell-specific targeting. These nanomedicine strategies offer compelling paths forward for developing more effective and targeted therapies for neurodegenerative diseases.